Mesothelioma - a growing medical problem with heterogeneous course - Chudzik, Robert; Pawelec, Sławomir; Matuszewski, Piotr; Piróg, Paweł; Rybojad, Beata; Mendrek-Sim, Magdalena; Boguniecki, Jakub; Rybojad, Paweł (Journal of Education, Health and Sport, 2019)
Mesothelioma is one of the most malignant neoplasms affecting the thin lining of the body's internal organs, known as the mesothelium. The incidence of mesothelioma in recent years has increased. It is assumed that the reason for this situation is the exposure in the past to natural mineral fibers (nickel, beryllium, silica dust), ionizing radiation, some organic compounds and SV40 virus but mostly to asbestos. The time from contact to the first symptoms is about 20-40 years. Probably the peak of morbidity is yet to come. Due to non-specific symptoms such as chest pain, shortness of breath, fluid in the pleural cavity, early detection is very difficult. Additionally, we can deal with mesothelioma which starting point is outside the pleural cavity. In such cases, diagnostics is even more difficult, because the only remaining symptom is pain. Therefore, it is important to pay attention to this growing problem.